Mechanical properties of granite under real-time high temperature and three-dimensional stress. (December 2020) - Ma, Xiao; Wang, Guiling; Hu, Dawei; Liu, Yanguang; Zhou, Hui; Liu, Feng
Abstract: Knowledge of mechanical properties of rocks under real-time high temperature and three-dimensional stress is critically important for stability analysis in Hot Dry Rock. In this context, the effects of temperature and horizontal stress on the mechanical behaviors of granite were investigated. A series of triaxial compression tests were performed on granite samples under real-time high temperature (up to 400 °C) by a self-developed real-time high temperature true triaxial test system. The test results showed that the mechanical properties of studied granite first increase before some temperature threshold, and then decrease with increasing temperature. The brittle characteristics of studied granite observed under low horizontal stress and room temperature are attenuated with increasing stress and temperature. Furthermore, observation of the fracture morphology of the samples indicates that the biotite particles undergo toughness enhancement at elevated temperature, which is the main reason for the reduction of rock brittleness and reinforcement in mechanical properties with increasing temperature. Finally, the effects of real-time high temperature on cohesion and internal friction angle were analyzed and compared with the previous test results of cohesion and internal friction angle of the samples subjected to pre-treatment of high temperature. A sound difference in cohesion and little difference in the internal friction angle were observed between the two cases. The test results could improve our understanding of the impact of temperature and stress on the mechanical properties of granite.